IMPLEMENTATION OF DIGITAL EMPLOYMENT SERVICES THROUGH THE SIHUBIN APPLICATION AT THE SIDOARJO MANPOWER OFFICE - Izati, Salsabila Aulia; Choiriyah, Ilmi Usrotin (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze the implementation of digital-based employment services through the Industrial Relations Information System (SIHUBIN) application at the Sidoarjo Regency Manpower Office. Digital transformation in the public service sector requires effectiveness, efficiency, and transparency, so it is important to examine how this application is run to support the improvement of service quality. Method: The research uses a descriptive qualitative approach with data collection techniques through in-depth interviews, field observations, and documentation studies. The analysis was carried out with reference to Charles O. Jones' theory of policy implementation which includes three aspects: organization, interpretation, and application. Results: The results of the study show that the implementation of SIHUBIN has not been optimal. From the organizational side, institutional support is available, but it is constrained by limited human resources, lack of technical training, and the lack of a regular maintenance budget. In terms of interpretation, the understanding of apparatus and users is still low due to less directed socialization. Meanwhile, in the application aspect, some services still rely on manual procedures, such as the absence of electronic receipts and limited access to online documents. Novelty: This study contributes by integrating the analysis of the implementation of SIHUBIN using the theoretical framework of Charles O. Jones, so that it can highlight the inhibiting and supporting factors more comprehensively. The research recommendations emphasize the importance of strengthening apparatus capacity, sustainable budgeting, and public communication strategies so that SIHUBIN can become an effective, efficient, and accountable digital service instrument.